2012
DOI: 10.1111/j.1399-3054.2012.01568.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical parameters controlling waterlogging stress tolerance in Prunus before and after drainage

Abstract: Waterlogging is associated with poor soil drainage. As a consequence oxygen levels decrease in the root environment inducing root asphyxia and affecting plant growth. Some plants can survive under these conditions triggering complex anatomical and biochemical adaptations, mostly in the roots. Long- and short-term responses to waterlogging stress were compared in two trials using a set of two myrobalans (Prunus cerasifera Erhr), 'P.2175' and 'P.2980', as tolerant rootstocks and two almond × peach [Prunus amygda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Excess water reduces oxygen (O 2 ) availability in plant roots, causing a barrier for gas diffusion into plant cells, inhibiting free gas exchange for photosynthesis and respiration and inducing changes in plant water relations (SanchezBlanco et al, 1994;Drew, 1997;Amador et al, 2012). Several anatomical, physiological and molecular changes due to flooding have been described, including: epinasty, wilting leaves (Kawase, 1981;Sanchez-Blanco et al, 1994;Dennis et al, 2000), premature leaf senescence, stem deformation, shoot length alteration and leaf area reduction (Aloni and Rosenshtein, 1982;Schaffer et al, 1992;Robbani et al, 2006).…”
Section: Waterlogging Causes Anatomical Physiological and Molecular mentioning
confidence: 99%
“…Excess water reduces oxygen (O 2 ) availability in plant roots, causing a barrier for gas diffusion into plant cells, inhibiting free gas exchange for photosynthesis and respiration and inducing changes in plant water relations (SanchezBlanco et al, 1994;Drew, 1997;Amador et al, 2012). Several anatomical, physiological and molecular changes due to flooding have been described, including: epinasty, wilting leaves (Kawase, 1981;Sanchez-Blanco et al, 1994;Dennis et al, 2000), premature leaf senescence, stem deformation, shoot length alteration and leaf area reduction (Aloni and Rosenshtein, 1982;Schaffer et al, 1992;Robbani et al, 2006).…”
Section: Waterlogging Causes Anatomical Physiological and Molecular mentioning
confidence: 99%
“…In nature it is common that plants under a flooding condition is first subjected to an hypoxic condition where oxygen decreases gradually to reach the condition of anoxia, which gives time to the plants to generate defense responses before the environmental condition becomes lethal (Drew, 1997). Response of sensitive rootstocks to water logging, such as the peach-almond hybrids 'Felinem' and 'Garnem' exhibit increased activity of defense enzymes against oxidative damage as compared to tolerant Myrobalan plum rootstocks (Amador et al, 2012). They found that it was not possible to establish a direct relationship among the activity of the enzymes: peroxidase (POD), superoxide dismutase (SOD) and catalase (CAT), and tolerance to water logging conditions.…”
Section: Scion-rootstock Graft Incompatibilitymentioning
confidence: 99%
“…Webb × Prunus persica [L.] Batsch) (Martinazzo et al, 2011), apricot (P. armeniaca) (Domingo et al, 2002;Nicolás et al, 2005), peach (Insausti and Gorjón, 2013), in peach-almond interspecific crosses and Prunus cerasifera Ehrh. (Xiloyannis et al, 2002), and the peach-almond hybrids 'Felinem' and 'Garnem' rootstocks (Amador et al, 2012).…”
Section: Scion-rootstock Graft Incompatibilitymentioning
confidence: 99%
See 2 more Smart Citations